Correction to: The PanSurg-PREDICT Study: endocrine surgery during the COVID-19 Pandemic - Van,den Heede K; Chidambaram,S; Beatty,JW; Chander,N; Markar,S; Tolley,NS; Palazzo,FF; Kinross,JK; Di,Marco AN (World Journal of Surgery, 2021)
Correction to: World J Surg https://doi.org/10.1007/s00268-021-06099-z